Prevalence of tobacco use and awareness about its ill-effects amongst adult rural population of district Rewari - Yadav, Preeti; ., Anjali; Yadav, Pooja (International Journal Of Community Medicine And Public Health, 2022)
Background: To determine the extent of tobacco use and knowledge of its harmful consequences among the rural population of District Rewari, Haryana. Methods:A cross-sectional study was done in the month of November 2021. A total 600 participants were interviewed using a pre-designed questionnaire for data collection. Results: 23.3% of population consuming tobacco, with male population has highest tobacco consumption (84.97%). Tobacco consumption is in form of Bidi and Hookah (85.1%). People who tried quitting tobacco restarted due to withdrawal symptoms (64.3%), peer pressure (24.2%), and 11.5% due to other factors like stress, gastric problems. 29.5% females and 25.3% males find tobacco as the main cause of oral cancer. 94% of people consuming tobacco were aware about its ill-effects. 14.37% recognized swelling and ulcers, 3.27% red and white lesion, 1.64% hoarseness of voice as main symptoms of oral cancer, while, 76.8% didn’t recognize any. 84.8% were never educated about causes, and early signs and symptoms of oral cancer by any healthcare professional, But the majority knows the ill effects of tobacco through advertisements and social media. Conclusions: Although tobacco consumption has decreased so far even in the villages, people are still unaware of the risks associated with smoking, and those who wish to stop can’t, due to lack of any professional help. New programs should be implemented like organizing awareness camps. Strictly banning the advertisements and marketing of tobacco products is the most necessary step in eliminating it from our society completely.